Teacher pedagogical competence in the implementation of the independent curriculum in The Pilot State Kindergarten of South OKU District - Primanisa, Reiska; Lestari, Tri; Yuberti, Yuberti (Al-Athfaal: Jurnal Ilmiah Pendidikan Anak Usia Dini, 2024)
Background: This research aims to describe in depth the pedagogical competence of teachers in implementing the independent curriculum. This research is qualitative research with a descriptive approach, in this case observing the pedagogical competence of teachers in implementing the independent curriculum in the Pilot State Kindergarten, South OKU Regency.Aim: This approach aims to provide a comprehensive overview of teachers' pedagogical competence in implementing the independent curriculum in the Pilot State Kindergarten, South OKU Regency.Method: This research uses observation, interview and documentation data collection techniques. Meanwhile, the data analysis technique in this research uses three stages according to Miles and Huberman, in the form of data reduction, data presentation, drawing conclusions.Results: This can be seen from several indicators such as mastery of students' character, educational learning, curriculum development, development of students' potential, communication with students, as well as assessment and evaluation. However, there are some teachers who have not fully mastered the pedagogical competency indicators. In implementing the independent curriculum, learning is divided into three main activities, namely opening, core and closing, which must be integrated into one learning series.Conclusion: The results of this research indicate that the pedagogical competence of teachers in implementing the independent curriculum in the Pilot State Kindergarten in OKU Selalan Regency is in the good category.